GAYA BAHASA SIMILE DALAM NOVEL INGKAR KARYA BOY CANDRA - Laila Tri Lestari; Sari Ani (LPPM UNISDA, 2022)
Abstact: Language style is very important for conveying meaning in a sentence that is used in everyday life. Whether or not the style of language used will have implications for people's assessment of the way of speaking and the meaning to be conveyed. This study uses a stylistic approach in analyzing the use of signs and understanding the meaning. The purpose of this study is to describe the results of the study of the analysis of the form of expression, the type of reference and the function of the use of simile style in Boy Candra's novel Ingkar. Based on the theory of Keraf and Pradopo. The results of the study show that the forms of expression, types of references and functions of the simile style in the novel of refusal vary, namely the use of words such as, as if, bak, like and express descriptions. The types of references in the simile style include body parts, human traits and animal traits. The function of the simile style in the novel Ingkar by Boy Candra describes the condition of the body, human nature and animal nature, compares objects in concrete and abstract terms, describes situations or situations and human nature.